Contrasting morphology and training background in waterpolo teams of different competitive levels - Sofia Canossa; José Arturo Abraldes; Susana Soares; María Helena Vila; Carmen Ferragut; Nuria Rodríguez; Francisco Manuel Argudo; Ricardo Jorge Fernandes; Júlio Manuel Garganta (Universidade Estadual Paulista (UNESP), 2014)
We aimed to describe and compare the general morphological, somatotype and training background characteristics of Iberian waterpolo players (22 Portuguese and 22 Spanish National Teams players) considering their playing positions. The International Working Group of Kinanthropometry guidelines was herein followed, and a somatochart was obtained through specific software (Somatotype, Calculation and Analysis. (c)2001 SWEAT technologies). Spanish players train more hours per week (22.8 ±9.5 vs.12.2 ±5.6), are taller (187.4 cm ±6.6 vs.180.3 cm ±5.1), heavier (89.2 kg ±11.6 vs.79.1 kg ±10.0), show higher arm span (195.7 cm ±8.5 vs.185.2 cm ±7.4) and muscle mass percentage (49.0% ± 1.8 vs.46.0% ±6.0), and tend to be more mesomorphic (5.19 ±1.27 vs.4.26 ±1.32) than the Portuguese players. Concerning field positions, Spanish center forward players train more hours per week than the Portuguese (20.2 ±9.1 vs.12.2 ±3.8) and show higher arm span (204.4 cm ±7.3 vs.184.0 cm ±6.5). Spanish goal keepers and outside players show higher muscle mass percentage (49.8% ±1.5 vs.42.2% ±5.2 and 49.4% ±1.5 vs.45.5% ±4.6, respectively) than the Portuguese players. These evidences should be taken into account for the improvement of waterpolo sport.